2011
DOI: 10.1017/s0373463310000470
|View full text |Cite
|
Sign up to set email alerts
|

Can Low-Cost Road Vehicles Positioning Systems Fulfil Accuracy Specifications of New ADAS Applications?

Abstract: Some new Advanced Driver Assistance Systems (ADAS) need on-the-lane vehicle positioning on accurate digital maps, but current applications of vehicle positioning do not justify the surcharge of very accurate equipment such as DGPS or high-cost inertial systems. For this reason, the performance of GPS in autonomous mode is analyzed. Although satisfactory results can be found, in some areas the GPS signal is lost or degraded so it is necessary to know the positioning error when using only inertial system data. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Technological advances in the last years have improved the precision of geolocalization systems [1] while reducing their costs. This has allowed the data obtained from geographical positioning systems to be implemented more efficiently in the automotive field.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in the last years have improved the precision of geolocalization systems [1] while reducing their costs. This has allowed the data obtained from geographical positioning systems to be implemented more efficiently in the automotive field.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method to obtain the necessary variables for autonomous vehicle control is based on adding to the detected points of the reference element, the portion of the reference element that is behind the vehicle and is not detected by the laser scanner. Since the use of GNSS is not feasible due to the inaccuracy of the measurement if differential corrections are not available [44] and because of the possible signal losses in some environments, or it is not possible to identify fixed landmarks in the infrastructure in an open and highly changing environment, the proposed method estimates the trajectory of the vehicle by studying the driving variables, such as steering wheel rotation and speed. Thus, the vehicle's position can be determined referred to its current position, so the previous measurements of the laser scanner are reproduced from the past regarding this new position and are integrated with the new detections.…”
Section: Slam Problemmentioning
confidence: 99%
“…This positioning is performed using a GPS receiver. However, numerous publications have shown that on many occasions GPS positioning is lacking in the reliability and precision required by safety applications [46], showing errors that are unacceptable for positioning on lanes or crossings. For this reason, we have used the information supplied by an RTK DGPS Topcon GB-300 receiver with an update frequency of 10 Hz and the possibility of using American GPS and Russian GLONASS that generates positions with an accuracy of less than 1 m. The GPS receiver transmits latitude/longitude positions to the computer.…”
Section: Collision Avoidance Systemmentioning
confidence: 99%